Analisis Keabsahan Muslim Mengucapkan Selamat Hari Raya Natal Berdasarkan Kaidah Niat - Normand Edwin Elnizar (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2023)
The fiqh rule regarding intention is the basic rule that is agreed upon as the first order. The formula is al-umūr bi maqāsidihā (the law of each case depends on its purpose/purpose/intention). The contents explain the purpose or intention as the basis for the assessment. This well-established rule has sufficient strength to become an argument for a fatwa for the permissibility of Muslims wishing Christians a Merry Christmas. This qualitative research takes data from literatures. The first step in content analysis in this research is mapping the arguments including fiqh principles what are involved in reasoning the fatwas about saying 'Merry Christmas' as a Christian holiday. Furthermore, the research will analize the results of the mapping based on the intention rule.